Gene expression changes associated with myocarditis and fibrosis in hearts of mice with chronic chagasic cardiomyopathy - Soares, Milena Botelho Pereira; Lima, Ricardo Santana de; Rocha, Leonardo Lima; Vasconcelos, Juliana Fraga; Rogatto, Silvia Regina [UNESP]; Santos, Ricardo Ribeiro dos; Iacobas, Sanda; Goldenberg, Regina Coeli; Iacobas, Dumitru Andrei; Tanowitz, Herbert Bernard; Carvalho, Antonio Carlos Campos de; Spray, David Conover (Oxford University Press (OUP), 2010)
Chronic chagasic cardiomyopathy is a leading cause of heart failure in Latin American countries. About 30% of Trypanosoma cruzi-infected individuals develop this severe symptomatic form of the disease, characterized by intense inflammatory response accompanied by fibrosis in the heart.We performed an extensive microarray analysis of hearts from a mouse model of this disease and identified significant alterations in expression of ~12% of the sampled genes. Extensive up-regulations were associated with immune-inflammatory responses (chemokines, adhesion molecules, cathepsins, and major histocompatibility complex molecules) and fibrosis (extracellular matrix components, lysyl oxidase, and tissue inhibitor of metalloproteinase 1). Our results indicate potentially relevant factors involved in the pathogenesis of the disease that may provide newtherapeutic targets in chronic Chagas disease. © 2010 by the Infectious Diseases Society of America.
Keywords: actin binding protein; beta3 integrin; cathepsin; cathepsin H; cathepsin S; CD11b antigen; CD38 antigen; CD4 antigen; CD52 antigen; CD8 antigen; cell adhesion molecule; cell surface protein; chemokine; chemokine receptor; chlordane; cytokine receptor; galectin 3; gamma interferon; intercellular adhesion molecule 1; interleukin 10 receptor alpha; matrix metalloproteinase 14; metalloproteinase inhibitor; PADGEM protein; protein lysine 6 oxidase; tumor necrosis factor alpha; animal cell; animal experiment; animal model; animal tissue; cell proliferation; Chagas disease; chronic disease; controlled study; female; gene expression; heart failure; heart muscle; heart muscle fibrosis; histocompatibility complex; immune response; immune response gene; immunohistochemistry; inflammation; intracellular signaling; male; microarray analysis; mouse; myocarditis; nonhuman; nucleotide sequence; pathogenesis; phosphate transport; priority journal; Trypanosoma cruzi; upregulation